The Spiderwick Chronicles : Great Escape, Special Edition of The Seeing Stone With Exclusive Lost Chapter - DiTerlizzi, Tony and Black, Holly (New York Simon & Schuster Books for Young Readers, 2007)
Jared, his twin brother Simon and their sister Mallory escape from trolls who are after a book that reveals the world of the fairies.
Include illustration
Keywords: Brothers and sisters -- Goblins -- Single-parent families